International economics : theory and policy - Krugman, Paul R.; Obstfeld, Maurice (Reading, Mass. : Addison-Wesley, 2000)
Krugman and Obstfeld provide a unified model of open-economy macroeconomics based upon an asset-market approach to exchange rate determination with a central role for expectations.
Includes bibliographical references and index.
oif 16/10/14; opc 30/08/16
Loans
Keywords: International economic relations; International finance